Menciptakan Rezim Perdagangan Bebas yang Adil: Sebuah Pendekatan Teori Keadilan - Dwi Hastuti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam Jember, 2016)
This article purposes to knowthe free trade regime from the perspective of Rawls's justice and create a free trade regime of the approach Rawls's theory of justice. This article argues that free trade must be based on a theory of justice by John Rawls (justice as fairness). the principle of Rawls If equality and freedom not reached when there is still inequality in social and economic conditions, it is necessary preferentialthe disadvantaged. Results of analysis showed that free trade regime in the provisions of the WTO has not yet adopted a principles of justice by John Rawls. An attempt to create a fair free trade regime that provides a special and different treatment to the developing countries by providing a greater advantage. Furthermore the institutional reform in the decision-making procedures more fair.